1992
DOI: 10.1177/0022487192043002003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Preservice Teachers' Perspectives on Diversity

Abstract: Case studies of six preservice teachers were conducted to assess their emerging perspectives about the problems that confront diverse learners in classrooms, their commitment to teaching diverse learners, and their beliefs about the causes of failure for diverse learners. Students' perceptions of the influences on their perspectives including the course work, their background experiences, contrasting field experiences, and their entering perspectives are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 7 publications
1
61
0
Order By: Relevance
“…Programs for preservice teachers that strive to create a "cultural consciousness" have been described by numerous authors (e.g., Colangelo, Dustin, & Foxley, 1985;Larke, Wiseman, & Bradley, 1990;McDiarmid, 1990;Noordhoff & Kleinfeld, 1993;Ross & Smith, 1992;Smolkin, Surnia, & Mercado, 1995). These multicultural programs attempt to change the beliefs and pedagogical practices of preservice teachers through short-term programs, course work on multiculturalism throughout the preservice program, extended informational sessions about various groups of individuals, or programs that are embedded within a culturally diverse community.…”
Section: Multicultural Preservice Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Programs for preservice teachers that strive to create a "cultural consciousness" have been described by numerous authors (e.g., Colangelo, Dustin, & Foxley, 1985;Larke, Wiseman, & Bradley, 1990;McDiarmid, 1990;Noordhoff & Kleinfeld, 1993;Ross & Smith, 1992;Smolkin, Surnia, & Mercado, 1995). These multicultural programs attempt to change the beliefs and pedagogical practices of preservice teachers through short-term programs, course work on multiculturalism throughout the preservice program, extended informational sessions about various groups of individuals, or programs that are embedded within a culturally diverse community.…”
Section: Multicultural Preservice Programsmentioning
confidence: 99%
“…Paine (1990) and Ross and Smith (1992) found that preservice teachers held different orientations and complex beliefs about diversity. Paine (1990) found that a preservice teacher could hold one of four orientations about diversity: (1) an individual orientation in which differences among students are attributed to their individual characteristics; (2) a categorical orientation in which differences among students are recognized as a result of their membership within a cultural group; (3) a contextual orientation in which differences among students are a result of society and are socially constructed; or (4) a pedagogical orientation in which students are recognized as contextually different and implications are made for learning and teaching.…”
Section: Multicultural Preservice Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…McIntosh (1988) and Sleeter (1995) 1992; Heinemann, Obi, Pagano, & Weiner, 1992; argue that no amount of multicultural knowledge Sleeter, 1995). Wlodkowski (1995) (Chiang, 1994;Ross & (Marshall, 1998;Nel, 1992;Sleeter, 1995) To better answer these questions, we will also interview the practicing teachers who will work with these students. We concur with Ilmer et al (1997) …”
mentioning
confidence: 99%
“…According to Grant and Secada (1990:148) the greater the exposure and the more time spent on getting to know and to learn the intercultural content borne by the "other" the more successful his or her integration will be. The teachers are also responsible for this, because many times they become frightened of sociocultural diversity and thus they ignore or overlook the existence of cultural influences in the classroom (Gay, 2002), which results in them addressing diversity through an incomplete and flawed framework that promotes inequality (Ross and Smith, 1992).…”
Section: Discussionmentioning
confidence: 99%